Incidence of Familial Craniosynostosis Among Patients With Nonsyndromic Craniosynostosis. Issue 6 (September 2019) - Kalantar-Hormozi, Hadis; Abbaszadeh-Kasbi, Ali; Sharifi, Guive; Davai, Nazanin Rita; Kalantar-Hormozi, Abdoljalil
Abstract : Background: Craniosynostosis has an incidence of 1 in 2000 to 2500 live births, and is categorized into syndromic and nonsyndromic types. Nonsyndromic ones can be familial in which more than one of the family members are involved. Methods: This is a prospective study which is carried out from April 2015 to January 2018 in 2 academic hospitals. Those patients who had nonsyndromic craniosynostosis and completed medical follow-up were included in the study as well as their 1st degree relatives. Age of patients, gender, existing consanguineous marriage, type of deliveries, type of pregnancy (assisted reproductive technologies [ART] versus sexual intercourse), severity and type of craniosynostosis were gathered. Results: Ninety-four (46.0%), 58 (28.4%), 28 (13.7%), 16 (7.8%), and 8 (3.9%) of patients had trigonocephaly, scaphocephaly, anterior plagiocephaly, complex, and brachycephaly, respectively. A total number of 204 patients were included in the study. Of all 204 families which were included, 30 (14.7%) families had positive familial history. Familial patients were determined in 10, 15, 8, 1, and 5 patients with scaphocephaly, trigonocephaly, anterior plagiocephaly, rachycephaly, and mixed type. Male to female ratio was 2:1, 1.9:1, 1.3:1, 1:1, and 1:1 for scaphocephaly, trigonocephaly, anterior plagiocephaly, brachycephaly, and mixed craniosynostosis. Twelve (5.9%) women had applied ART. Conclusion: Present study reveals that metopic suture is the most frequent craniosynostosis within nonsyndromic types. All the types of nonsyndromic craniosynostosis had male prevalence but for complex one which was equal in both gender. Nonsyndromic craniosynostosis in about 14.7% of patients was familial. Abstract : Supplemental Digital Content is available in the text